2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5334683
|View full text |Cite
|
Sign up to set email alerts
|

Automated nodule location and size estimation using a multi-scale laplacian of Gaussian filtering approach

Abstract: Abstract-Estimation of nodule location and size is an important pre-processing step in some nodule segmentation algorithms to determine the size and location of the region of interest. Ideally, such estimation methods will consistently find the same nodule location irregardless of where the the seed point (provided either manually or by a nodule detection algorithm) is placed relative to the "true" center of the nodule, and the size should be a reasonable estimate of the true nodule size. We developed a method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…For example, in [21] Gaussian has been used for locate pulmonary nodules, and other studies have shown that the characteristic scale of a Laplacian of Gaussian (LoG) agreed well with radiologistsąŕ estimates of nodule size [22,23]. Kong et al [24] propose a generalized Laplacian of Gaussian (LoG) (gLoG) filter for detecting general elliptical blob structures in images,Miao et al [25] used rank order LoG filter for interest point detection, and Shi et al [2] proposed a dot enhancement filter by combining Hessian matrix and LoG filter.…”
Section: Related Workmentioning
confidence: 82%
“…For example, in [21] Gaussian has been used for locate pulmonary nodules, and other studies have shown that the characteristic scale of a Laplacian of Gaussian (LoG) agreed well with radiologistsąŕ estimates of nodule size [22,23]. Kong et al [24] propose a generalized Laplacian of Gaussian (LoG) (gLoG) filter for detecting general elliptical blob structures in images,Miao et al [25] used rank order LoG filter for interest point detection, and Shi et al [2] proposed a dot enhancement filter by combining Hessian matrix and LoG filter.…”
Section: Related Workmentioning
confidence: 82%
“…The intensity threshold is the oldest method that is based on measuring the absolute intensity difference between cells and black background, either by global or local adaptive thresholding. Another approach is feature detection, which uses image intensity-derived features that are found using linear image filtering or others such as Gaussian or Laplacian-of-Gaussian filters [45][46][47]. In contrast, the morphological filtering method uses e.g., nonlinear filters to examine geometrical and topological properties of objects within images.…”
Section: Computational Tools To Segment Images For Recognizing Cellsmentioning
confidence: 99%
“…However, all approaches described above use only the information from a single scale. Multi-scale approaches have been widely used for object detection in computer vision (e.g., [18], [19], [20]) and medical image analysis (e.g., [21], [22], [23], [24]). For detection of biological particles in microscopy images, a wavelet-based approach was introduced which uses information from multiple scales to increase the robustness to noise [25], [26].…”
mentioning
confidence: 99%